Asymmetric Relationship Between Income Inequality and Economic Growth in Nigeria - Pocho, Anthony Gabriel (Cattleya Darmaya Fortuna, 2025)
Nigeria’s case is ironic, with so much wealth both human and material yet inequality in income and poverty is evident. Therefore, this study focuses on the asymmetric relationship between income inequality and economic growth in Nigeria (1986-2022) with the intension of understanding whether growth reduces or increases income inequality. The study explored the Non-linear Autoregressive Distributed lag (NARD) model approach with the intent of enabling both the short run and long run asymmetric effect. The findings indicated that, asymmetry is only obvious in the long run and that the early stage of growth does not reduce income inequality. However, in the long run evidence of growth reducing income inequality abounds if the growth reaches 5.5% as indicated by the outcome of Kuznets turning point. Based on these findings the study recommends that; poverty alleviation programmes should be targeted at the real poor and such programmes should last enough to make real impact. Public institutions saddled with the responsibility of equipping the youths with skills should be well funded and giving the freedom they deserve to function effectively. Access to quality higher education should be widen and affordable, because when people are educated at this level there are better chances for economic mobility.